Field validated prediction of latent slope failure based on cracked soil approach - S. Alexsander; I.B. Mochtar; W. Utama (Lowland Technology International, 2018)
This study is to prove the existence of latent sliding of a suspected unstable slope using the cracked soils approach. This study was initiated by trying to map the cracks inside soil slope by means of measuring the Tomographic Resistivity, TR, and Induced Polarization, IP, of the soil at the slope prior to performing stability analysis of the slope. To map the cracks inside the slope at the study location, 3 lines of TR and IP were performed. The results of the 3-line mapping showed the existence of sliding plane toward the slope edge at a depth between 3 – 5 meters below the soil surface, and the sliding plane was about 30 – 50 meters in length. With the cracks and possible sliding planes were known, the cracks could be drawn in 3-dimentional model, as part of the topographical map of the slope. This study had predicted that another slope sliding would occur at the area where the highest stresses and strains concentration were located. It was at this location exactly that another slope sliding had occurred several months afterwards when heavy rain came.